Psychoeducational training to increase self-esteem in adolescents at Panggon Sinau Reading Park Boyolali - Athiyallah, Arina; Kurniawati, Rafidhah; Anwar, Anwar; Purwandari, Eny (Community Empowerment, 2021)
Factors that affect the level of self-esteem is a low level of education, and low economic status. Psychoeducational programs have been widely used to provide information that combines psychotherapy with education, which aims to increase literacy and knowledge about personality development and psychological well-being. The purpose of this activity is to develop and increase the self-esteem of teenagers in Panggon Sinau Reading Park. The method used was a psychoeducational program that provides understanding and knowledge about self-esteem. This program used an experimental design by conducting pre-test and post-test on adolescents aged 16-23 years. Community service through psychoeducational programs has succeeded in increasing self-esteem knowledge in adolescents.